1977
DOI: 10.1172/jci108902
|View full text |Cite
|
Sign up to set email alerts
|

Generation of the combined prothrombin activation peptide (F1-2) during the clotting of blood and plasma.

Abstract: A B S T R A C T We have investigated the pathway of prothrombin activation in blood and plasma. By means of a rapid purification procedure involving chromatography on DEAE-cellulose and hydroxyapatite, we demonstrated that the major prothrombin fragment in serum is that representing the amino-terminal half of prothrombin (i.e. FL 2). The F1 2 isolated was characterized by its size, amino acid and antigenic compositions, amino-terminal residue, and the peptides (designated Fl and F2, respectively) it yielded up… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
47
0
1

Year Published

1985
1985
2010
2010

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 118 publications
(50 citation statements)
references
References 20 publications
2
47
0
1
Order By: Relevance
“…Despite the short incubation time, the sensor yielded a 220% fluorescence increase in serum compared with the 270% fluorescence gain obtained in buffer at 750 nM thrombin concentration. We found that the background signals were noticeably larger in undoped serum compared to buffer; given that the FBS used in the experiment was harvested from calves in utero, we suspect that some activation of the blood-clotting cascade may have occurred, thereby producing detectable levels of thrombin in the serum (33). Similar background thrombin signal in serum has also been observed in related work (34).…”
Section: Resultssupporting
confidence: 76%
“…Despite the short incubation time, the sensor yielded a 220% fluorescence increase in serum compared with the 270% fluorescence gain obtained in buffer at 750 nM thrombin concentration. We found that the background signals were noticeably larger in undoped serum compared to buffer; given that the FBS used in the experiment was harvested from calves in utero, we suspect that some activation of the blood-clotting cascade may have occurred, thereby producing detectable levels of thrombin in the serum (33). Similar background thrombin signal in serum has also been observed in related work (34).…”
Section: Resultssupporting
confidence: 76%
“…Therefore a-thrombin plays a central role in the mechanism of blood coagulation. Incidentally, the concentrations of oc-thrombin used in this study were less than the ones found in spontaneously clotting human blood (circa 140 nM; Aronson et al, 1977). In addition, this enzyme also exerts hormone-like effects on a large number of cell types (Shuman, 1986).…”
Section: Discussionmentioning
confidence: 65%
“…Affected members of family VIII possessed the other major subtype of inherited antithrombin deficiency. This disorder is produced by a discrete molecular 22 antithrombin deficient subjects derived from these kindreds were studied in detail (Table I; Fig. 1).…”
Section: Resultsmentioning
confidence: 99%
“…After 90 min of incubation, the clot was removed, heparin (final concentration I U/ml) was added, and the suspension was stirred for an additional 5 min. Subsequently, F1+2 was isolated from the sera by DEAE-cellulose batch adsorption-elution and hydroxylapatite chromatography as described by Aronson et al (22). Examination of a series of fractions eluted from hydroxylapatite with a potassium phosphate concentration of 0.35-0.45 M, revealed that >90% of the resultant material was F1+2 as judged by the sodium dodecyl sulfate (SDS) gel electrophoretic technique of Laemmli (23).…”
Section: Methodsmentioning
confidence: 99%